2016
DOI: 10.1259/dmfr.20160047
|View full text |Cite
|
Sign up to set email alerts
|

Are there any differences in mandibular morphology of patients with bisphosphonate-related osteonecrosis of jaws?: a case-control study

Abstract: Objectives: The aim of this study was to compare the morphological differences in the mandible between patients with bisphosphonate-related osteonecrosis of the jaw (BRONJ) and healthy individuals and to detect the correlation between these parameters on panoramic radiography and CBCT. Methods: The CBCT and panoramic images of patients with BRONJ (n 5 32) and control groups (n 5 32) were included in the study. All the comparisons were analyzed between the osteonecrosed and healthy sides of patients with BRONJ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…This finding is reported only with assessment using cone beam CT (CBCT). 23,24 CBCT is known to be more useful for measuring the mandibular cortical bone 23 and other characteristic findings of BRONJ than PR. 23,25,26 We used only conventional CT in our study, and so we were unable to include thickness of cortical bone and degree of bone marrow sclerosis for findings of CT. CBCT has possibility to give additional information to conventional CT or PR.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is reported only with assessment using cone beam CT (CBCT). 23,24 CBCT is known to be more useful for measuring the mandibular cortical bone 23 and other characteristic findings of BRONJ than PR. 23,25,26 We used only conventional CT in our study, and so we were unable to include thickness of cortical bone and degree of bone marrow sclerosis for findings of CT. CBCT has possibility to give additional information to conventional CT or PR.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the MCT showing differences according to sex. Ozcan et al (2016) studied the morphological differences of the mandible in 32 healthy individuals and 32 individuals with BRONJ on their panoramic radiographs and CBCT images. In their study, they evaluated CA, GA, AGA, AGD and condyle and ramus height using panoramic radiography and used CBCT to evaluate MCI and bone quality index.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding panoramic radiography of MRONJ, Klingelhöffer et al [ 11 ] indicated that panoramic radiographs of patients undergoing antiresorptive therapy with manifested osteonecrosis more frequently showed changes in the bone structure. Ozcan et al [ 12 ] suggested that the osseous changes associated with BRONJ in the mandible, which includes the cortical and spongious bones, do not reflect the external morphology of the mandible on panoramic images. Torres et al [ 13 ] suggested that mandibular inferior cortical bone thickness in patients using bisphosphonates was detected on panoramic radiographs, and represented a potentially useful tool for the detection of dimensional changes associated with bisphosphonate therapy.…”
Section: Discussionmentioning
confidence: 99%